PENGARUH PEMBERIAN PESTISIDA ORGANIK TERHADAP PENEKANAN INTENSITAS HAMA PENGGEREK BATANG PADI KUNING (Scirpophaga incertulas) DAN HASIL PADI HITAM (Oryza sativa.L) - Endang Kantikowati; Karya; Poppy Noorliyanti (Program Studi Agroteknologi Faperta UNIBBA, 2021)
The study aims to determine the effect of organic pesticides on suppressing the attack of yellow rice stem borer (Scirpophaga incertulas) and black rice yields (Oryza sativa.L). The research was conducted at the Al Mukhlis Agricultural and Rural Training Center (P4S), from December 2016 until April 2017, altitude + 700 meters above sea level, soil type Latosol, pH 5.7, rainfall 25458 mm / year including C3 based on Oldeman's classification. The research method used a separate plot design with 2 factors, namely 3 application times (U) as the main plot, namely: U1 (5,10,15,30,35 HST), U2 (10,20,30,40,50 HST), U3 (12,24,36,48,60 HST) and 4 concentrations (K) as subplots, namely: K1 (0 ml / l,) K2 (5 ml / l), K3 (10 ml / l) and K4 (15 ml / l). The results showed that the treatment time of application of organic pesticide U1 (5,10.15,30,35 HST) and K4 concentration (15ml / l) gave a better effect on the intensity of yellow rice stem borer (Scirpophaga incertulas) attack